Penggunaan Bahan Organik Sebagai Pemikat Nyamuk - Suwarlan, Stivani Ayuning; Patrik, Jonathan; Desmond, Desmond; Purba, Elisabet; Septiana, Gracia Tiffany; Jenny, Jenny; Haryanto, John; Chian, Sung; Hie, Sung (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
This devotion is intended to provide the solution for society on the coast especially mangrove forests. We intend to solve the problem without any troubles that could impact the ecosystem by giving insight into how important the empowerment of mangrove, hence the development of mangrove ecotourism could be established properly. As time passed, we realized that Kalembak is more focusing on their mangrove?s program. Therefore, this fact could lead to an overpopulation of mosquito. They did admit that when evening, the mosquito just flocks around them. We decided to give an alternative for their problem, which is handmade organic mosquito repellent.  The methods are implemented using three-technique, which is preparation, implementation, and evaluation. Our product, which is made from organic materials such as brown sugar and yeast as a substitute of dangerous chemical products that could be found inside the typical mosquito repellent. The product is made from a mixture of brown sugar and yeast that could lead a fermentation, which will generate carbon dioxide that attracts the mosquitos. Hence lead to a fact that the more carbon dioxide around, the more mosquito around.